1989
DOI: 10.1007/bf02386194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disuse on the ultrastructure of the achilles tendon in rats

Abstract: We examined the influence exerted, through disuse of the hindlimb, on the collagen fibres of the achilles tendon in rats. With disuse the body mass decreased by 28%, and the mass of soleus muscle decreased by 20%. A decrease in the surface area and diameter was observed in the experimental group when compared to the control group. A histogram of the collagen fibres showed a decrease of the thick fibres in the experimental group. The maximum surface area of collagen fibres in the experimental group was seen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 13 publications
2
49
0
3
Order By: Relevance
“…Indeed, Vailas et al (1988) have indicated a decrease in the concentration of collagen and proteoglycans of the patellar tendon of the rat after HS. Moreover, Nakagawa et al (1989) have reported that HS induced a decrease in both surface area and diameter of collagen ®bres from the tendon of the rat soleus muscle. Both results would induce an increase in compliance of tendon structures.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, Vailas et al (1988) have indicated a decrease in the concentration of collagen and proteoglycans of the patellar tendon of the rat after HS. Moreover, Nakagawa et al (1989) have reported that HS induced a decrease in both surface area and diameter of collagen ®bres from the tendon of the rat soleus muscle. Both results would induce an increase in compliance of tendon structures.…”
Section: Discussionmentioning
confidence: 98%
“…9 Karpakka et al 15 reported that activities of prolyl 4-hydroxylase and galactosylhydroxylysyl glucosyltransferase, which are used for estimating alterations in the rate of collagen biosynthesis under different experimental and clinical conditions, decreased after 3 weeks of immobilization. Nakagawa et al 19 showed that decreased thickness of collagen fibers at the Achilles tendon resulted from disuse. They concluded that this decrease of collagen fiber thickness leads to a decrease in tensile strength.…”
mentioning
confidence: 99%
“…They concluded that this decrease of collagen fiber thickness leads to a decrease in tensile strength. The biochemical studies by Karpakka et al 15 and Nakagawa et al 19 showed that there were changes in the tensile strength of series elastic components following disuse secondary to orthopaedic surgery in humans. Widrick and Fitts 35 reported a reduction of muscle fiber stiffness following a period of nonweight bearing in rats.…”
mentioning
confidence: 99%
“…En estudios animales se evaluaron los efectos de la inmovilización del complejo grastrocnemius--soleus--aquiles en ratas [95] y los resultados fueron bastante drásticos.…”
Section: Efecto De La Inmovilización En La Unión Miotendinosaunclassified
“…Experimentos con animales, mostraron que la inmovilización durante cinco semanas resultó en una disminución del número de las fibras gruesas de colágeno, disminuyendo la media del diámetro de grosor de estas fibras [95].…”
Section: Efectos De La Inmovilización En El Tejido Tendinosounclassified